Framework for the implementation of knowledge sharing behavior in global software development organizations - Anwar, Rayhab (2019)
Focus of world has shifted from industrialization (industrial economy) to knowledge-based economy. An economy becomes knowledge economy when use and creation of knowledge becomes its integral part. Based on the importance of knowledge, it is considered as an asset for competitive advantage. The competitive advantage which is based on knowledge is more likely to sustain for a longer period as compared to competitive advantage which relies on non-knowledge-based resources like latest technology. Knowledge which is vital for economic development and competitive advantage needs to be managed. This managing of knowledge is known as knowledge management. Knowledge management is a process through which knowledge is obtained, created, shared and stored. All these steps of knowledge management heavily rely on knowledge sharing. If there is no knowledge sharing, knowledge cannot be created, obtained or stored. One of the key issues in the execution of knowledge sharing is due to the mindset of prevailing culture of “knowledge is power". Such a culture, in organizations sturdily affects organization’s growth and progress. Software industry is a highly competitive and innovative industry. In present era, software developers are globally distributed. Globally distributed software developers face cultural and geographic differences such as difference in language, traditions, values, norms of behavior and time zone difference which may cause misunderstanding and clashes. Knowledge sharing among distributed individuals is a complicated process; it involves many challenges and complications. The key focus of the existing literature has been on individuals working from same locations rather than globally distributed locations. The available literature focuses more on organizational aspects and neglects the geographic, cultural and psychological aspects of software developers working from globally distributed locations. Therefore, extensive research is required to understand the knowledge sharing process for globally distributed software development organizations. The purpose of this study is to fill this gap by identifying the problems being faced in the implementation of knowledge sharing behavior in global software development organizations. For this research “positivist” research philosophy was used, as the current framework was based upon utilization of existing theory. For data analysis structural equation modelling (SEM) has been adopted. The “measurement model” and the “structural model” is achieved by using “SmartPLS 3.0”. Geographic distance, linguistic distance and time zone difference were introduced as barriers. The results showed that geographic distance had negative impact on knowledge sharing behavior, whereas time zone difference and linguistic distance had insignificant impact on the knowledge sharing behavior. Motivation, social interaction and trust were introduced as facilitators. The results showed that social interaction and trust had positive impact on knowledge sharing behavior, whereas motivation had insignificant impact on knowledge sharing behavior. Two moderating factors were “organizational support” and “technological support” were introduced. organizational support emerged as a significant factor to support knowledge sharing behavior whereas “technological support” hypothesis was rejected. The study demonstrated a positive and strong relationship between “knowledge sharing behavior” and “job performance”.